TRENDS IN PUBLIC SERVICE RESEARCH IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Adekamwa, Adekamwa; Mursalim, Mursalim; Indrayanti, Indrayanti (Jurnal Administrasi Negara, 2024)
Public services in Indonesia face various challenges, including a complex bureaucracy, limited resources, and policy implementation that often does not align with field practices. This study aims to explore research trends in public services in Indonesia and identify factors that influence success and barriers to policy implementation and innovation. The method used was a Systematic Literature Review (SLR) of 30 selected publications from highly reputable national and international journals, focusing on the themes of service innovation, service quality, policy implementation, and leadership roles. The results show that the adoption of digital technology is increasing and is considered to be able to improve the transparency and efficiency of public services, although challenges such as limited resources and regulatory frameworks still hinder optimal adoption. In addition, good service quality is associated with increased public satisfaction and trust. The role of transformational leadership has proven to be a key factor in driving innovation and overcoming bureaucratic resistance. The implication is the need for an approach that includes technology integration, adaptive policy reform, and visionary leadership. This research is expected to serve as a foundation for future studies that emphasise a multidisciplinary approach to achieving continuous improvement in public services.